LEVERAGING E-WOM FOR CUSTOMER LOYALTY: POLICY INSIGHTS FROM AIDA STORE - Siti Nabila Fatimatuzzahro; Neka Fitriyah; Rahmi Winangsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The development of digital communication technology has given rise to electronic Word of Mouth (e-WOM) as a form of consumer communication that shapes customer loyalty. In the context of e-commerce, consumers tend to trust other consumers' reviews and experiences more than promotional information submitted by sellers. This research aims to understand the electronic Word of Mouth communication model applied by AIDA Store in shaping customer loyalty. This research uses a qualitative approach with descriptive methods. The informants in this study consisted of key informants, namely AIDA Store consumers, and supporting informants, namely shop owners. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The theory used to analyze the data is Integrated Marketing Communication (IMC) which is associated with the concept of customer loyalty. The results show that e-WOM communication in AIDA Store occurs naturally and involves a two-way communication process between consumers and stores. Findings based on the five main focuses show that: (1) consumers perceive AIDA Store's content to be attractive and unengineered; (2) consumers actively gather information through various digital platforms; (3) consumers feel comfortable consulting directly with the store; (4) online reviews have a strong emotional influence on purchasing decisions; and (5) consumers feel more confident after reading positive reviews. This process shows that consumer loyalty is formed gradually through a series of consistent, transparent and responsive communication experiences.